Simultaneous determination of ethinyl estradiol and drospirenone in oral contraceptive by high performance liquid chromatography - Viviane Benevenuti Silva; Angel Arturo Gaona Galdos; Cintia Maria Alves Mothe; Michele Bacchi Pallastrelli; Maria Segunda Aurora Prado; Anil Kumar Singh; Erika Rosa Maria Kedor-Hackmann; Maria Inês Rocha Miritello Santoro (Universidade de São Paulo, 2013)
A simple, rapid, economical and reliable high performance liquid chromatographic method has been developed and successfully applied in simultaneous determination of ethinyl estradiol and drospirenone in coated tablets. The HPLC method was performed on a LiChroCART® 100RP column (125x4 mm i.d., 5 µm) with acetonitrile:water 50:50 (v/v) as mobile phase, pumped at a flow rate of 1.0 mL.min-1. The fluorescence detection for ethinyl estradiol was made at λex= 280 nm and λem= 310 nm and a UV detection for drospirenone was made at 200 nm. The elution time for ethinyl estradiol and drospirenone were 4.0 and 5.7 min, respectively. The method was validated in accordance to USP 34 guidelines. The proposed HPLC method presented advantages over reported methods and is suitable for quality control assays of ethinyl estradiol and drospirenone in coated tablets.